Risk analysis model for construction projects using fuzzy logic - Chaher, Zid Chaher; Soomro, Ali Raza (2016)
The construction industry project is more subjective and risky compared with the others industries because of the unique characteristics of construction activities such as poor working condition, the significant frequency of accidents and the occupational risky situation. Risk analysis and management on the project sites is the first key to achieve adequate level of security. However, the modern construction and the new sophisticated design have shown a significant obstacles and uncertainties to complete the project safely; thereby it is inevitable to search a new approach to deal with uncertainties. The ability of a fuzzy system to deliver its reasoning process is presented to have absolute result within the field of risk analysis. As well as, fuzzy set theory is mainly subjective and associated to deal with inexact and vague information in construction projects. This paper describes the stages of the fuzzy risk analysis model which is developed to assess the risks related with construction projects and their uncertainties based on evaluations of cost, time and quality. Ultimately, using this model we can prioritize and rank all risk factors cited in the construction project; besides that we can easily manage them in the best appropriate way.